Adiwiyata Program for Students in the Study of Psychology of Learning and Ecological Counseling Guidance - Nur Azizah; Adhitya Ridwan Budhi Prasetyo Nugroho (Jurnal Educative: Journal of Educational Studies, 2020)
Researchers have conducted studies on the planning, implementation, management and evaluation of the Adiwiyata program in the context of school activities. However, a specific analysis has not been identified in the field of Learning Psychology and Environmental Counseling. The aim of this study is therefore to analyze the Adiwiyata program in the study of Learning Psychology and Ecological Guidance. This literature study was conducted by analyzing the primary sources of the Regulation of the Minister of the Environment of the Republic of Indonesia No. 05 of 2013 on the Guidelines for the Implementation of the Adiwiyata Program and No. P.52/Menlhk/Setjen/Kum.1/9/2019 on the Movement of Environmental Care and Culture in Schools (PBLHS Movement). The results showed that the psychology of learning of the Adiwiyata programme could be integrated into the learning process as well as educational facilities for students using the school environment by considering the psychological development of the students. In the meantime, the Adiwiyata program in the study of ecological counseling guidance can be internalized in creating programs or applied in guidance and counseling services for students to solve the problems and to form students' self-awareness and environmental awareness. Kajian penerapan program Adiwiyata mulai dari perencanaan, pelaksanaan, pengelolaan, serta evaluasi maupun penerapan dalam kegiatan di sekolah telah banyak dilakukan. Namun belum ditemukan analisis spesifik dalam kajian psikologi belajar dan bimbingan konseling ekologi. Oleh karena itu, penelitian ini bertujuan menganalisis program Adiwiyata bagi siswa dalam kajian psikologi belajar dan bimbingan konseling ekologi. Metode yang digunakan adalah studi kepustakaan dengan menganalisis sumber primer dari Peraturan Menteri Lingkungan Hidup Republik Indonesia Nomor 05 Tahun 2013 Tentang Pedoman Pelaksanaan Program Adiwiyata dan Nomor P.52/Menlhk/Setjen/Kum.1/9/2019 Tentang Gerakan Peduli dan Berbudaya Lingkungan Hidup di Sekolah (Gerakan PBLHS). Hasil penelitian menunjukkan program Adiwiyata berdasarkan kajian psikologi belajar dapat diintegrasikan dalam proses belajar mengajar maupun sarana edukasi siswa melalui pemanfaatan lingkungan sekolah dengan mempertimbangkan perkembangan psikologis siswa. Sedangkan Program Adiwiyata dalam kajian bimbingan konseling ekologi bisa diinternalisasi dalam pembuatan program maupun diaplikasikan dalam layanan bimbingan dan konseling bagi siswa untuk mendapatkan solusi atas masalahnya maupun membentuk kesadaran diri siswa maupun kesadaran pada lingkungan.